Precision spherical nucleic acids for delivery of anticancer drugs. Issue 9 (12th July 2017) - Bousmail, Danny; Amrein, Lilian; Fakhoury, Johans J.; Fakih, Hassan H.; Hsu, John C. C.; Panasci, Lawrence; Sleiman, Hanadi F.
Abstract : Highly monodisperse sequence-defined spherical nucleic acids (HE12 –SNAs ) for delivery of small-molecule anticancer drugs. Abstract : We report a spherical nucleic acid (SNA) system for the delivery of BKM120, an anticancer drug for treatment of chronic lymphocytic leukemia (CLL). While promising for cancer treatment, this drug crosses the blood–brain barrier causing significant side-effects in patients. The DNA nanoparticle encapsulates BKM120 in high efficiency, and is unparalleled in its monodispersity, ease of synthesis and stability in different biological media and in serum. These DNA nanostructures demonstrate efficient uptake in human cervical cancer (HeLa) cells, and increased internalization of cargo. In vitro studies show that BKM120-loaded nanoparticles promote apoptosis in primary patient CLL lymphocytes, and act as sensitizers of other antitumor drugs, without causing non-specific inflammation. Evaluation of this drug delivery system in vivo shows long circulation times up to 24 hours, full body distribution, accumulation at tumor sites and minimal leakage through the blood–brain barrier. Our results demonstrate the great potential of these delivery vehicles as a general platform for chemotherapeutic drug delivery.